Tinjauan Yuridis terhadap Tindak Kriminal Prostitusi Digital yang dilakukan oleh Pekerja Seks Komersial Melalui Aplikasi - Lestari, Wahyu Tri (UM Purwokerto Press, 2024)
The development of information technology and the internet has changed people’s lifestyle towards a modern one. The availability of the internet makes it easier to access information and transaction, but it also has negative impacts such as cybercrime. One phenomenon that has emerged is online prostution, where the practice of prostution is carried out through electonic or social media. The Mi Chat application is one of platfroms most widely used for online prostution in Indonesia. The research method applied in this research is a qualitative method using a normative juruducal approach. This approach is used to understand the law related to problem and its application. The research results show that there are several factors that influence someone to fall into online prostution, such as economic problems, lifestyle, low education, and an unsupportive family environment.